Intentional news avoidance on short-form video platforms: a moderated mediation model of psychological reactance and relative entertainment motivation - Runxi Zeng; Siting Guo; Richard Evans (Humanities & Social Sciences Communications, 2024)
Abstract Previous studies have identified a correlation between individuals’ perception of news quality and their intention to avoid political news. However, limited research exists that examines the mechanisms that mediate or moderate this relationship, particularly in the context of short-form video platforms. This study, using a sample of 523 active users of Douyin, a Chinese short-form video platform, addresses this gap by examining the mediating influence of psychological reactance and the moderating impact of relative entertainment motivation on the connection between perceived news quality and intentional news avoidance. The study finds that the negative association between perceived news quality and intentional news avoidance is mediated by psychological reactance, while both the direct effect of perceived news quality on intentional news avoidance, and the indirect effect through psychological reactance, are moderated by relative entertainment motivation. Specifically, these effects are stronger for individuals with high relative entertainment motivation. These findings suggest that if users possess high relative entertainment motivation, their psychological reactance and intentional news avoidance can be reduced if the quality of news improves. This study contributes to current understanding of users’ deliberate avoidance of news and offers insights for owners and developers of short-form video platforms and algorithms.